EVALUATION OF THE IMPLEMENTATION OF THE TEACHING FACTORY PROGRAM OF SMKN 6 PADANG - Mala Maulidina pratiwi; Ruhul Fitri Rosel; Ambiyar; Fahmi Rizal (Institute of Computer Science (IOCS), 2022)
Vocational High Schools (SMK) are required to be able to improve the quality of graduates by increasing practical learning programs, but basically the implementation of practice in schools is still not optimal which makes graduates not in accordance with what is needed by the industrial world. teaching factory is referred to as a factory in a school where the process and suggestions for learning through practice are in accordance with the industrial world. Teaching factory is expected to be a solution to be able to create vocational graduates in accordance with industry standards. However, in the implementation of the factory teaching program there will always be obstacles and problems, so evaluation is needed. The purpose of this research is to find out how the teaching factory program runs so that it is always good. The type of research used is descriptive with a qualitative approach. qualitative descriptive method with the subjects in this study were teachers and students of SMK N 6 Padang. The results of the research evaluation can be seen that the CIPP model, known as the factory teaching program, has been running well. Based on research on the evaluation of the teaching factory program at SMK N 6 Padang, overall the teaching factory program has been implemented well, although it is not perfect, there are still things that must be improved and developed so that the teaching factory implementation can run well. factory continues to run well in accordance with the objectives of the factory teaching program.